The Effectiveness of Ecological Intelligence-Based Indonesian Language Textbooks on the Environmentally Friendly Behaviors of State Junior High School Students in Surakarta - Suwandi, S; Yunus, A; Rahmawati, L E (KnE Social Sciences, 2018)
This research aims to investigate the effectiveness of ecological intelligence-based Indonesian language textbooks on state junior high school students’ environmentally friendly behaviors. This study applies an experimental method. The research population is the 7th-grade students of state junior high schools in Surakarta. Samples were taken using cluster random sampling. Data were collected using the observation technique. The observation technique and instruments were used to gather data regarding students’ environmentally friendly behaviors. Validation of the research instruments was carried out using construct validity. Data were analyzed using a t-test with a significance level of 5%. Based on the results of data analysis, this research concludes that ecological intelligence-based Indonesian language textbooks significantly influence students’ environmentally friendly behaviors. Keywords: ecological intelligence, environmentally friendly behaviors, Indonesian language